Cyprus energy policy: The road to the 2006 world renewable energy congress trophy - Maxoulis, Christos N.; Kalogirou, Soteris A. (My University, 2008)
Cyprus is a small island situated in the north-eastern Mediterranean with no indigenous conventional energy sources, away from interconnected networks of electricity and gas. Recently, Cyprus won the prestigious World Renewable Energy Congress Trophy for its remarkable efforts and initiatives to increase the contribution of renewable energy sources (RES) to the county's energy mix. This paper presents the energy system of Cyprus, analyses and reviews the energy policy and the various measures taken by the government for the development and support on the use of RES in the island, which had a decisive role on the judges’ decision for the nomination of the award.
Keywords: Renewable energy sources; WREC trophy; Sustainability